2017
DOI: 10.1021/acs.jnatprod.6b00783
|View full text |Cite
|
Sign up to set email alerts
|

Glycybridins A–K, Bioactive Phenolic Compounds from Glycyrrhiza glabra

Abstract: In an attempt to discover bioactive agents from the herbal medicine Glycyrrhiza glabra (widely known as licorice), 11 new phenolic compounds, glycybridins A-K (1-11), along with 47 known phenolics (12-58) were isolated. Their structures were elucidated on the basis of extensive NMR and MS analyses as well as experimental and computed ECD data. According to the clinical therapeutic effects of licorice, enzyme or cell-based bioactivity screenings of 1-58 were conducted. A number of compounds significantly activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Particularly active were prodelphinidins and procyanidins from the fruit pericarp of Clausena lansium Skeels [102], as well as the complex mixtures isolated from Persea Americana [106], Longan bark [99], and from leaves and fruit of Leucaena leucocephala [97]. Very potent (IC50 values in the range 0.10-7.5 μM) mushroom tyrosinase inhibitors have been isolated from licorice (Figure 12), the most active belonging to the isoflavan class [108][109][110]. A pterocarpan (IC 50 = 16.7 µM) and some isoflavones and isoflavans isolated from Dalbergia parviflora ( Figure 11) have been also recently reported as inhibitors of the diphenolase activity of mushroom tyrosinase [95].…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
See 1 more Smart Citation
“…Particularly active were prodelphinidins and procyanidins from the fruit pericarp of Clausena lansium Skeels [102], as well as the complex mixtures isolated from Persea Americana [106], Longan bark [99], and from leaves and fruit of Leucaena leucocephala [97]. Very potent (IC50 values in the range 0.10-7.5 μM) mushroom tyrosinase inhibitors have been isolated from licorice (Figure 12), the most active belonging to the isoflavan class [108][109][110]. A pterocarpan (IC 50 = 16.7 µM) and some isoflavones and isoflavans isolated from Dalbergia parviflora ( Figure 11) have been also recently reported as inhibitors of the diphenolase activity of mushroom tyrosinase [95].…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Particularly active were prodelphinidins and procyanidins from the fruit pericarp of Clausena lansium Skeels [102], as well as the complex mixtures isolated from Persea Americana [106], Longan bark [99], and from leaves and fruit of Leucaena leucocephala [97]. Very potent (IC 50 values in the range 0.10-7.5 µM) mushroom tyrosinase inhibitors have been isolated from licorice (Figure 12), the most active belonging to the isoflavan class [108][109][110] IC50 values in the range 28-42 μM have been reported for two lignans isolated from Opilia amentacea leaves [112] (Figure 13), whereas particularly effective against the monophenolase activity of the enzyme were flavonolignans from the seeds of Silybum marianum (IC50 in the range 1.7-4.9 μM) ( Figure 13) [113] as well as, although with a lower strength, hydroxylated phenones from Syzygium polyanthum leaves [114] (Figure 14). IC 50 values in the range 28-42 µM have been reported for two lignans isolated from Opilia amentacea leaves [112] (Figure 13), whereas particularly effective against the monophenolase activity of the enzyme were flavonolignans from the seeds of Silybum marianum (IC 50 in the range 1.7-4.9 µM) ( Figure 13) [113] as well as, although with a lower strength, hydroxylated phenones from Syzygium polyanthum leaves [114] (Figure 14).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…The known chalcones (4 -8) were also reported to show cytotoxicity. [17 -19][21] [23] In combination with the reported data, it seems that chalcones with alkylated chain at ring A (7) [21] possessed lower cytotoxicity than those with alkylated group at ring B (1 -6 and 8). [17 -19][23] However, it is necessary to do further research to clarify the structure-activity relationship.…”
Section: Cytotoxicity Assaymentioning
confidence: 89%
“…Paeonia lactiflora (Ma et al, ), Panax ginseng (Bak et al, ), and Coffea arabica (Cavin et al, ) are examples of such herbs. Apigenin (a flavonoid in some Apiaceae herbs; Sang et al, ), galangin (found in some Zingiberaceae rhizomes; Huang et al, ), glycybridin A & G ( Glycyrrhiza glabra ; K. Li et al, ), lycopene (Hedayati et al, ), and cyanidin (an anthocyanin found in different berry fruits; De Pascual‐Teresa, ) are a few examples of natural substances that have been reported to interact with Nrf2, potentially presenting health promoting properties.…”
Section: Introductionmentioning
confidence: 99%